(untitled) (Research, Society and Development, 2020)
Currently, on the world stage and in Brazil, there is an increase in the number of breast cancer diagnoses, which has a major impact on public health and on the quality of life of these patients. Thus, it is necessary for nurses to be present in multidisciplinary actions from prevention to treatment, demonstrating their functions in the management of care, education and psychosocial support for these patients. The objective is to report the role of nurses in relation to women diagnosed with breast cancer. It is an integrative review with eight articles selected in the LILACS and SciELO databases between the period 2010 and 2020. After reading, analyzing and interpreting the data, the publications show different challenges faced by nurses in the care of diagnosed patients breast cancer, its role being indispensable in guiding the disease. Knowing the barriers related to the adequate treatment of physical and psychosocial illness, among other demands in the social context, can be an important tool in the search for ways to offer more quality assistance to this population.